2021
DOI: 10.1136/bmjgh-2020-004075
|View full text |Cite
|
Sign up to set email alerts
|

Community-level spillover effects of an intervention to prevent intimate partner violence and HIV transmission in rural Ethiopia

Abstract: BackgroundIntimate partner violence (IPV) is associated with adverse health and psychosocial outcomes. We analysed the spillover effects of Unite for a Better Life (UBL), an intervention evaluated in a cluster randomised controlled trial using a double-randomised design; previous evidence suggests UBL reduced IPV in rural Ethiopia among direct beneficiaries.MethodsVillages (n=64) were randomly allocated to control, or to receive UBL delivered to men, women or couples. Each cluster comprised 106 surveyed househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In line with this review's specific focus on interventions that commenced on or after 2000, the earliest included publication was Legovini (2005) and the most recent was Leight et al (2021). The annual number of publications saw a steady increase over the years with 89 (65% of the total) published between 2016 and 2021.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In line with this review's specific focus on interventions that commenced on or after 2000, the earliest included publication was Legovini (2005) and the most recent was Leight et al (2021). The annual number of publications saw a steady increase over the years with 89 (65% of the total) published between 2016 and 2021.…”
Section: Resultsmentioning
confidence: 87%
“…According to the Q $Q$‐test, there was no significant amount of heterogeneity in the true outcomes (Q(7)=6.47 $Q(7)=6.47$, p=0.49 $p=0.49$, τˆ2=0.00 ${\hat{\tau }}^{2}=0.00$, I2=0.00 ${I}^{2}=0.00$%), thus we did not test for moderation. One study (Leight et al, 2021) had a relatively large weight compared to the rest of the studies (i.e., weight3/k $\text{weight}\ge 3/k$, so a weight at least 3 times as large as having equal weights across studies). An examination of the studentized residuals revealed that none of the studies had a value larger than ±2.73 $\pm 2.73$ and hence there was no indication of outliers in the context of this model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In addition, a separate analysis examined the diffusion of the intervention effects to the 20% of individuals enrolled in the trial who were not invited to participate in the intervention. 24 Evidence suggests that women in the intervention communities who were not sampled for participation in the intervention reported a decline in experience of past-year IPV of comparable magnitude to that reported for intervention participants. In fact, the hypothesis that the direct and indirect effects are identical cannot be rejected.…”
Section: Randomised Controlled Trialmentioning
confidence: 93%